„Wrocław. Escape Room” — groza w teatrze lalek dla dorosłych - Joanna Królikowska (Literatura i Kultura Popularna)
The article concerns the graduation puppet performance Wrocław: Escape Room, directed by Arkadiusz Buszko from the National Academy of Theatre Arts in Kraków at the Puppetry Department in Wrocław. The narrative of the performance is set in post-apocalyptic Wrocław, and the heroes are historic figures connected with this city at various stages of their lives. An analysis of the performance, with particular emphasis on the role and form of puppets, animated objects and costumes, made it possible to assess how the staging concepts of the creators contributed to the horror effect and how they influenced the presentation of the characters. The authors of the Wrocław diploma piece utilized the puppets’ potential for formal transformations in creating characteristic, fascinating, but also quite frightening puppets and costumes made of fragments of mannequins. Therefore, the analysis of the elements of the performance was supplemented with considerations on the mannequins and their role in the theatre. The second category that is significant for the interpretation of the performance is the notion of a monster. Research on the perception of monsters in culture proved to be helpful, as it allowed for reading the characters of the performance through the lens of monstrosity.